Health care financing in Nigeria: national health accounts perspective (2014)
The paper investigated the funding pattern of healthcare in Nigeria based on the National Health Accounts framework. Two rounds of National Health Accounts estimation covering the eight-year period, 1998-2005 were analyzed in this paper. The first round covering 1998-2002 was funded by donors and characterized by limited access to data, which accounted for its seeming underestimation. The second round funded by Federal Ministry of Health enjoyed access to wider data set, and allowed for state level sub- National Health Accounts estimates covering 17 out of 36 states of the federation. The estimates generally revealed that the households constitute the main source of financing healthcare in the Nigeria, accounting for over 66% of Total Health Expenditure, while government contributes average of 29%. Though resource pooling through health insurance appreciably grew over the years, it is still at its infancy, contributing minimally to Total Health Expenditure. While the private facilities dominates in the provision of healthcare service in the first round, the second round estimates shows that more than half of health care services were provided in the public facilities. Despite preventive care through Primary Health Care being the pillar of the National Health Policy strategy, curative care continued to dominate Total Health Expenditure in the country. The process of second round estimation accorded the issue of institutionalization a priority place, which resulted in the identification and training of state focal persons for possible integration of regular National Health Accounts data collection into public service practices. The absence of continuity in funding by government is threatening the ownership of the process. While the Nigeria Total Health Expenditure is highest in Africa, her per capita Total Health Expenditure and as percentage of GDP is well below figure for some African countries.